2014
DOI: 10.1890/13-2347.1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of intraguild predation in predicting emergent multiple predator effects

Abstract: Prey typically coexist with multiple predator species, each of which presents a predation risk related to its habitat domain and foraging mode. These predator characteristics can be used to predict how the risk from multiple predators will combine to create emergent multiple predator effects for shared prey. Interactions between predators, particularly intraguild predation, can strongly alter prey suppression, though the importance of intraguild predation in multiple predator effects has not been explicitly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…Alternatively, under elevated wolf spider densities, warming-associated increases in spider activity could result in more frequent antagonistic interactions with other predators (66). Strong predator-predator interactions or even intraguild predation, which is fairly common in this system (22), can relax the collective effect of predator communities, resulting in increased prey populations and weaker trophic cascades (67,68). Under warming, we observed that numbers of intermediate predators declined as wolf spider densities increased (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Alternatively, under elevated wolf spider densities, warming-associated increases in spider activity could result in more frequent antagonistic interactions with other predators (66). Strong predator-predator interactions or even intraguild predation, which is fairly common in this system (22), can relax the collective effect of predator communities, resulting in increased prey populations and weaker trophic cascades (67,68). Under warming, we observed that numbers of intermediate predators declined as wolf spider densities increased (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Increased longevity in response to predator cues has not previously been documented, but may be related to interactions between Tigrosa and Scarites. Tigrosa is the more dangerous predator for Pardosa (Sitvarin, unpublished data), though Scarites is capable of interfering with and consuming Tigrosa (Sitvarin & Rypstra 2014). Therefore, Pardosa may interpret Scarites cues as a forthcoming reduction in predation risk, leading to decreased levels of stress hormones or elevated levels of hormones that counter the effects of stress hormones.…”
mentioning
confidence: 99%
“…The main orders constituting Lycosid diets in our study were Diptera, Hemiptera, Hymenoptera and Lepidoptera. Interestingly, spiders, harvestmen and carabid beetles were also found in spider gut contents which confirms the potential of NoSpi2 for the investigation of intraguild predation, which has often been documented among spiders and for carabid beetles feeding on spiders (Lang, 2003;Davey et al, 2012;Sitvarin & Rypstra, 2014). Although coleopterans have been reported as spider prey (HambĂ€ck et al, 2016), predation of carabid beetles by spiders has not been observed so far.…”
Section: Discussionsupporting
confidence: 58%